Shadow Banks and Profitability: An Empirical Analysis of China’s Shadow Banking - Cao, Kangquan (2014)
This paper provides an empirical analysis of the factors that determine the profitability of Chinese shadow banks from the year 2006 to 2013. The tested sample includes 10 investment banks, 10 trust companies and 8 securities companies. There are two dependent variables including return on average assets (ROAA) and return on average equity (ROAE). The results, obtained by applying the system-GMM estimator to the panel of 28 shadow banks, indicate that bank-specific factors and external factors have significant relations to shadow banks profitability: company with higher capital adequacy, which is measure as equity-to-asset ratio, tends to have higher profitability; cost-to-income ratio that measures management efficiency has positive relationship with profitability; liquidity and size of shadow bank perform a negative relation to profitability, which is opposite to the expected direction. In terms of external factor, GDP growth rate, inflation and interest rate are all presenting a positive relationship with profitability. The bank asset-to-GDP ratio (ASSGDP) is surprisingly showing a positive relationship with profitability, which indicates that the Chinese shadow banking industry arguably remains under developed and relatively lower inter competitions.